Factors underlying membrane potential-dependent and -independent fluorescence responses of potentiometric dyes in stressed cells: diS-C(3)(3) in yeast - Gásková, D; Cadek, R; Chaloupka, R; Plásek, J; Sigler, K (Biochimica et biophysica acta, 2001)
The redistribution fluorescent dye diS-C(3)(3) responds to yeast plasma membrane depolarisation or hyperpolarisation by Delta psi-dependent outflow from or uptake into the cells, reflected in changes in the fluorescence maximum lambda(max) and fluorescence intensity. Upon membrane permeabilisation the dye redistributes between the cell and the medium in a purely concentration-dependent manner, which gives rise to Delta psi-independent fluorescence responses that may mimic Delta psi-dependent blue or red shift in lambda(max). These lambda(max) shifts after cell permeabilisation depend on probe and ion concentrations inside and outside the cells at the moment of permeabilisation and reflect (a) permeabilisation-induced Delta psi collapse, (b) changing probe binding capacity of cell constituents (inverse to the ambient ionic strength) and (c) hampering of probe equilibration by the poorly permeable cell wall. At low external ion concentrations, cell permeabilisation causes ion outflow and probe influx (hyperpolarisation-like red shift in lambda(max)) caused by an increase in the probe-binding capacity of the cell interior and, in the case of heat shock, protein denaturation unmasking additional probe-binding sites. At high external ion levels minimising net ion efflux and at high intracellular probe concentrations at the moment of permeabilisation, the Delta psi collapse causes a blue lambda(max) shift mimicking an apparent depolarisation.
Keywords: Oxidative Stress; permeabilita buněčné membrány; oxidační stres; Saccharomyces cerevisiae; Carbocyanines; Fluorescent Dyes; Potentiometry; membránové potenciály; fluorescenční barviva; Cell Membrane Permeability; potenciometrie; Membrane Potentials; karbocyaniny